The Effect of Leverage, Firm Size, Profitability and Political Connections on Income Smoothing - Windy Angraeni; Elvin Bastian; Tri Lestari (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to determine the effect of leverage, firm size, profitability and political connections on income smoothing with firm value as a moderating variable. The approach used in this research is a quantitative approach. The data in this study are secondary data and data obtained from the site www.idx.go.id and company performance reports. The sampling technique used was purposive sampling technique with a total sample of 90 observation data from manufacturing companies in the consumer goods industry sector in 2016-2020. The data analysis technique uses multiple linear regression analysis using SPSS version 23 program. The results of this study indicate that the Leverage variable has no effect on income smoothing, while Company Size, Profitability and Political Connections affect income smoothing. For the moderating variable, firm value is proven to be able to moderate Leverage and Profitability, and not able to moderate the variables of Firm Size and Political Connections.